Defective Kernel 1 (DEK1) is required for three‐dimensional growth in Physcomitrella patens. Issue 3 (21st May 2014) - Perroud, Pierre‐François; Demko, Viktor; Johansen, Wenche; Wilson, Robert C.; Olsen, Odd‐Arne; Quatrano, Ralph S.
Summary: Orientation of cell division is critical for plant morphogenesis. This is evident in the formation and function of meristems and for morphogenetic transitions. Mosses undergo such transitions: from two‐dimensional tip‐growing filaments (protonema) to the generation of three‐dimensional leaf‐like structures (gametophores). The Defective Kernel 1 (DEK1) protein plays a key role in the perception of and/or response to positional cues that specify the formation and function of the epidermal layer in developing seeds of flowering plants. The moss Physcomitrella patens contains the highly conserved DEK1 gene. Using efficient gene targeting, we generated a precise PpDEK1 deletion ( ∆dek1 ), which resulted in normal filamentous growth of protonema. Two distinct mutant phenotypes were observed: an excess of buds on the protonema, and abnormal cell divisions in the emerging buds resulting in developmental arrest and the absence of three‐dimensional growth. Overexpression of a complete PpDEK1 cDNA, or the calpain domain of PpDEK1 alone, successfully complements both phenotypes. These results in P. patens demonstrate the morphogenetic importance of the DEK1 protein in the control of oriented cell divisions. As it is not for protonema, it will allow dissection of the structure/function relationships of the different domains of DEK1 using gene targeting in null mutant background.